ANALYSIS OF JOB PERMANENCE TIME OF FORMAL WORKERS ON LABOR MARKET IN FEDERAL DISTRICT OF BRAZIL VIA COX PROPORTIONAL HAZARD AND LOG-NORMAL MODELS - SANTOS, Rayany de Oliveira; NAKANO, Eduardo Yoshio (Brazilian Journal of Biometrics, 2015)
In this work, we propose to analyze survival data from formal labor market in Federal District of Brazil by log-normal regression and the Cox proportional hazard models. The objective was to estimate the distribution of job permanence time of these workers through a dataset. The large number of observations made unfeasible the use of traditional hypothesis testing and graphic techniques were used for decisions. Both log-normal and Cox models presented an appropriate adjustment for the considered data set.